MANAGEMENT TRANSFORMATIONS IN CONDITIONSOF UNCERTAINTY - Joe, Andrean (E-Journal VFU, 2025)
This study investigates effective leadership strategies in small and medium-sized enterprises (SMEs) in Germany against the backdrop of ongoing digital and cultural transformations. Particular emphasis is placed on transformative leadership as a dynamic response to organizational change in uncertain environments and as a catalyst for aligning business models with circular economy principles. The primary objective is to identify critical psychological and structural success factors that foster sustainable development in SMEs. The empirical analysis focuses on four key sectors: the real estate industry, financial consult-ing agencies, craft enterprises, and tax advisory firms. Special attention is given to the inter-play between digital competencies and cultural adaptability in shaping resilient leadership practices.